Less Familiar Pathways in Constructivism - Parida, B. K.; Mohapatra, J. K.; Mahapatra, M. (INDIAN EDUCATIONAL REVIEW, 2011)
Beginning as an art movement in Russia in the early parts of the twentieth century, constructivism has encompassed many domains of knowledge. Accordingly, many varieties of constructivism have appeared in the literature, so much so that some authors have gone on to dub constructivism a ‘veritable jungle’. The five major varieties such as philosophical constructivism, sociological constructivism, Piagetian constructivism, radical constructivism, and social constructivism are like well travelled highways, widely talked about and discussed in literature. In the present paper we make an effort to bring into focus some of the less discussed varieties of constructivism. Though they are like less travelled streets compared to their major counterparts, they lead to new destinations, and explore new dimensions of knowledge acquisition and cognition.